Regularities of chemical elements distribution in soils of gold mine "Pioner" of the Amur region - Mikhail Lyapunov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is caused by the need to receive the data of analysis of territory ecological-geochemical situation for a deposit further development. The main aim of the study: to determine the concentration of chemical elements and compounds in the soil horizons (humus) and (illuvial) before the "Pokrovskiy mine" business activities related to "Pioner" industrial refining; based on the results of the geoecological studies to assess soil horizon state by total pollution. The methods used in the study: spectral semiquantitative and atomic absorption method; atomic emission and massspectral analysis of moving forms. The results: The author has assessed the state of soil horizons А and В by total pollution rate (rate setting on the maximum permissible concentrations). The distribution of chemical elements high concentrations on the field was determined. Based on the results of the geoecological research within the gold mine "Pioner" the status assessment of soil horizons was carried out. Soil humus horizon, assessed by its total pollution rate, has all polluted areas. Areas with low pollution level occupy 22 % of the studied area, with an average pollution level - 48 %, with strong - 23 %, with very strong - 7 %. With distance from the field the concentration of ore bearing items decreases, but it is not allowed within the investigated area. Soil illuvial horizon within "Pioner" gold mine, assessed according to its total pollution rate, has all polluted areas. Areas with low pollution level occupy 10 % of the studied area, with an average pollution level - 43 %, with strong - 24 %, with very strong - 23 %. Higher concentrations of chemical elements are more distributed in the illuvial horizon relative to the humus one. The data obtained can be used in the analysis of ecological-geochemical situation for further development of the deposit.